BRANDING SUMBA BARAT MELALUI MEDIA INTERAKTIF BERBASIS KEARIFAN LOKAL BUDAYA PASOLA UNTUK PENGEMBANGAN PARIWISATA DI KABUPATEN INI - Intan Djaha; Rini Darmastuti (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
Indonesia is a country that is rich in culture and has values and philosophies of life-based on local wisdom of that culture. One of the cultural treasures of Indonesian society is Pasola culture which is owned by the people of West Sumba. By using qualitative research methods and ethnographic approaches, this study aims to analyze and give understanding to millennials about the meaning and message of Pasola, and to make the outside community interested in Pasola. The results of this study are first, Pasola is an ancestral tradition in the form of rituals to bring blessings, soil fertility and improve relations between kabisu / ethnic groups. Second, the values taught through local wisdom Pasola become the identity of the West Sumba community and become a brand in the development of regional tourism. Third, Branding West Sumba tourism can be done by using interactive media based on local wisdom of Pasola.